EFFECTIVENESS OF INTERNAL COMMUNICATION OF THE HEALTH HUMAN RESOURCES SECTION OF CIVIL SERVANTS IN THE STUDY ASSIGNMENT AND STUDY PERMIT PROGRAM (QUALITATIVE DESCRIPTIVE STUDY AT BANDAR LAMPUNG CITY HEALTH OFFICE) - Evadianti, Yuli; Ulfa, Maria (Universitas Sang Bumi Ruwa Jurai, 2023)
The Health Resources Sector is one of the Sectors in the Bandar Lampung City Health Service which is a benchmark for the quality of health workers in increasing the professionalism of health workers by improving education. Study assignments and study permits are under the Health Human Resources Department which is administrated to serve recommendations for study permits and study assignments. The problem in this research is how effective internal communication occurs in the Health Human Resources Section at the Bandar Lampung City Health Service. In writing this thesis, we use the Interpersonal Communication Theory approach with the concept of Internal Communication Theory. The researcher used a descriptive qualitative research method, with two key informants and four informants. The results of this research are that for vertical communication, the Head and also employees who hold general functional and specific functional positions (paramedics and doctors) use vertical communication and horizontal communication in disseminating information related to existing work. The effectiveness of internal communication must also be of a nature. open communication, empathy, mutual support and equality. The conclusion is that internal communication at the Bandar Lampung City Health Service in the Health Human Resources Section is effective in improving study assignment and study permit program services.